Transformational Leadership and Employee Satisfaction on Employee Loyalty: The Mediating Role of Employee Engagement - Wardana, I Made Aditya; Salain, Putu Pradiva Putra; Dwinata JS, I Putu Wahyu (Jurnal Manajemen Bisnis, 2024)
Research aims: This study investigates employee loyalty among hospitality businesses despite improvements after the pandemic. It scrutinizes the influence of transformational leadership on employee satisfaction, engagement, and loyalty and assesses the mediating role of employee engagement.Design/Methodology/Approach: A quantitative design was implemented, and data were collected employing a questionnaire circulated to 261 employees. Then, the accumulated data was investigated using the Smart PLS 3.2.9 application.Research findings: The study highlights that transformational leadership affects employee loyalty while employee satisfaction does not. Employee engagement mediates the linkage between transformational leadership and employee satisfaction and loyalty. Employees need satisfaction to cover their turnover chances and remain loyal.Theoretical Contribution/Originality: The study expands the existing literature concerning the role of transformational leadership and job satisfaction in reinforcing employee loyalty. This type of study is infrequently due to its significant focus on performance.Practitioners/Policy Implications: Hotel business managers pay more attention to employee engagement in every activity. Accordingly, employee loyalty can be maintained, impacting hotel performance.Research Limitations/Implications: This study was performed on the four-star hotels. Consequently, these results cannot be fully implemented in different businesses. Various further elaborations are required to make it applicable to different sectors.